Professional situation of the Ukrainian actors during the Russian aggression against Ukraine - Huth, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The paper presents the professional situation of Ukrainian actors after the outbreak of war in February 2022. The data presented here concern the different needs and possibilities of supporting Ukrainian actors living abroad and those displaced within Ukraine. The article presents possible differences in the situation of actors in Ukraine and abroad and how much chance Ukrainian actors currently have to follow up on their acting career.